2017
DOI: 10.1089/mdr.2015.0361
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Mutations in the Antimicrobial Target Genes Related to Levofloxacin, Clarithromycin, and Amoxicillin Resistance inHelicobacter pyloriIsolates from Buenos Aires City

Abstract: Domain V of 23S rRNA, gyrA and gyrB Quinolones Resistance-Determining Region (QRDR), and pbp-1A gene point mutations were investigated in Helicobacter pylori-resistant isolates from three centres of Buenos Aires. Minimal inhibitory concentrations (MICs) were performed in 197 isolates from 52 H. pylori-positive naive patients by agar dilution method. Point mutations were achieved by amplification and sequencing of the target genes, and their association with resistance was determined by natural transformation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 45 publications
2
43
6
1
Order By: Relevance
“…25 De Palma et al reported that resistance of levofloxacin was due to substitution at position 87 (K,I) and 91 (G,N,A) of gyrA QRDR in the 92.8% of the resistant isolates. 40 Miftahussurur et al reported that mutations at Asn-87 and/or Asp-91 were predominantly in levofloxacinresistant strains, and the gyrB mutation had a steady relationship with gyrA 87-91 mutations. 41 None of the substitutions found in gyrB proved conferring resistance in this study.…”
Section: Discussionmentioning
confidence: 99%
“…25 De Palma et al reported that resistance of levofloxacin was due to substitution at position 87 (K,I) and 91 (G,N,A) of gyrA QRDR in the 92.8% of the resistant isolates. 40 Miftahussurur et al reported that mutations at Asn-87 and/or Asp-91 were predominantly in levofloxacinresistant strains, and the gyrB mutation had a steady relationship with gyrA 87-91 mutations. 41 None of the substitutions found in gyrB proved conferring resistance in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, their detection has been done in H. pylori bacteria recovered from human clinical specimens. 14,48,51 The final part of our survey focused on the genotyping of vacA, cagA, cagE, iceA, oipA, and babA alleles of the H. pylori bacteria. We also originated that vacA s1a, s2, m1a, and m2, and iceA1 and cagA, s1am1a, s2m1a, s1am2, s2m2, and s1a/cagA-/iceA1/oipA-/cagE-/babA-, m1a/cagA-/ iceA1/oipA-/cagE-/babA-, s2/cagA-/iceA1/oipA-/cagE-/ babA-, s1a/cagA+/iceA1/oipA+/cagE-/babA-, m1a/cagA +/iceA1/oipA+/cagE+/babA-, m1a/cagA+/iceA1/oipA +/cagE-/babA-, m2/cagA-/iceA1/oipA-/cagE-/babA-, s1a/ cagA+/iceA1/oipA+/cagE+/babA-, s1a/cagA-/iceA1/oipA-/ cagE+/babA-, s1a/cagA-/iceA1/oipA+/cagE-/babA-, s1b/ cagA-/iceA1/oipA-/cagE-/babA-, m1a/cagA-/iceA1/oipA-/ cagE+/babA-, m1a/cagA-/iceA1/oipA+/cagE-/babA-, m1b/ cagA-/iceA1/oipA-/cagE-/babA-, s1a/cagA+/iceA1/oipA-/ cagE+/babA-, s2/cagA+/iceA1/oipA+/cagE-/babA-, s2/ cagA-/iceA1/oipA-/cagE+/babA-, s2/cagA-/iceA1/oipA+/ca gE-/babA-, m1a/cagA+/iceA1/oipA-/cagE-/babA+, and m1a/cagA+/iceA1/oipA-/cagE+/babA-were the most generally perceived genotypes amongst the H. pylori bacteria.…”
Section: Combined Genotyping Patterns Distribution* (%)mentioning
confidence: 99%
“…11,13 The presence of certain antibiotic resistance genes, particularly rdxA, pbp1A, gyrA, and cla which encode resistance toward metronidazole, amoxicillin, fluoroquinolone, and clarithromycin antibiotic agents, respectively, is one of the most important reasons for occurrence of antibiotic resistance. 14,15 Therefore, it is significant to know the exact phenotypic and genotypic patterns of antibiotic resistance of H. pylori bacteria recovered from foods with animal origins.…”
Section: Introductionmentioning
confidence: 99%
“…Among the 6 common mutations in gyrA that invoke fluoroquinolone resistance, N87 and D91 are reported to be the most commonly encountered (14,19,40), and these mutations were the most frequent gyrA mutations in our cohort (Table 4). However, we did not observe a significant correlation between gyrA mutations and treatment success.…”
Section: Discussionmentioning
confidence: 82%
“…Tetracycline resistance is due to mutation in the binding site of tetracycline in 16S rRNA (14). Fluoroquinolone resistance is due to point mutations in the quinolone resistance determining region (QRDR) of gyrA at positions encoding amino acids 86, 87, 88, 91, or 97 (14,19). We used 3 pairs of primers to amplify the three gene regions: gyrA, (forward) 5=-AAGGTTAGGCAGACGGCT-3= and (reverse) 5=-TTAACCACCCCCATGGCGA-3=; 23S rRNA gene, (forward) 5=-GGTGGTATCTCAAGGATGGC-3= and (reverse) 5=-GATCTAACCGCGGCAAGACG-3= (20); and 16S rRNA gene, (forward) 5=-TGGAGCATGTGG TTTAATTCGA-3= and (reverse) 5=-TGCGGGACTTAACCCAACA-3= (21).…”
Section: Methodsmentioning
confidence: 99%